Transarterial embolization (TAE) as add-on to percutaneous radiofrequency ablation (RFA) for the treatment of renal tumors: review of the literature, overview of state-of-the-art embolization materials and further perspective of advanced image-guided tumor ablation - Sommer, Christof-Matthias; Vollherbst, Dominik; Radeleff, Boris; Kauczor, Hans-Ulrich (European journal of radiology, 2017)
Percutaneous radiofrequency ablation (RFA) for the treatment of stage I renal cell carcinoma has recently gained significant attention as the now available long-term and controlled data demonstrate that RFA can result in disease-free and cancer-specific survival comparable with partial and/or radical nephrectomy. In the non-controlled single center trials, however, the rates of treatment failure vary. Operator experience and ablation technique may explain some of the different outcomes. In the controlled trials, a major limitation is the lack of adequate randomization. In case reports, original series and overview articles, transarterial embolization (TAE) before percutaneous RFA was promising to increase tumor control and to reduce complications. The purpose of this study was to systematically review the literature on TAE as add-on to percutaneous RFA for renal tumors. Specific data regarding technique, tumor and patient characteristics as well as technical, clinical and oncologic outcomes have been analyzed. Additionally, an overview of state-of-the-art embolization materials and the radiological perspective of advanced image-guided tumor ablation (TA) will be discussed. In conclusion, TAE as add-on to percutaneous RFA is feasible and very effective and safe for the treatment of T1a tumors in difficult locations and T1b tumors. Advanced radiological techniques and technologies such as microwave ablation, innovative embolization materials and software-based solutions are now available, or will be available in the near future, to reduce the limitations of bland RFA. Clinical implementation is extremely important for performing image-guided TA as a highly standardized effective procedure even in the most challenging cases of localized renal tumors.
Available online 2 November 2016
Gesehen am 25.07.2018